Predictors of segmental myocardial functional recovery in patients after an acute ST-Elevation myocardial infarction. Issue 112 (March 2019) - Mangion, Kenneth; Carrick, David; Clerfond, Guillaume; Rush, Christopher; McComb, Christie; Oldroyd, Keith G.; Petrie, Mark C.; Eteiba, Hany; Lindsay, Mitchell; McEntegart, Margaret; Hood, Stuart; Watkins, Stuart; et al.
Abstract: Objective: We hypothesized that Displacement Encoding with Stimulated Echoes (DENSE) and feature-tracking derived circumferential strain would provide incremental prognostic value over the extent of infarction for recovery of segmental myocardial function. Methods: Two hundred and sixty-one patients (mean age 59 years, 73% male) underwent MRI 2 days post-ST elevation myocardial infarction (STEMI) and 241 (92%) underwent repeat imaging 6 months later. The MRI protocol included cine, 2D-cine DENSE, T2 mapping and late enhancement. Wall motion scoring was assessed by 2-blinded observers and adjudicated by a third. (WMS: 1=normal, 2=hypokinetic, 3=akinetic, 4=dyskinetic). WMS improvement was defined as a decrease in WMS ≥ 1, and normalization where WMS = 1 on follow-up. Segmental circumferential strain was derived utilizing DENSE and feature-tracking. A generalized linear mixed model with random effect of subject was constructed and used to account for repeated sampling when investigating predictors of segmental myocardial improvement or normalization Results: At baseline and follow-up, 1416 segments had evaluable data for all parameters. Circumferential strain by DENSE (p < 0.001) and feature-tracking (p < 0.001), extent of oedema (p < 0.001), infarct size (p < 0.001), and microvascular obstruction (p < 0.001) were associates of both improvement and normalization of WMS. Circumferential strain provided incremental predictive value even after accounting for infarct size, extent of oedema and microvascular obstruction, for segmental improvement (DENSE: odds ratio, 95% confidence intervals: 1.08 per −1% peak strain, 1.05–1.12, p < 0.001, feature-tracking: odds ratio, 95% confidence intervals: 1.05 per −1% peak strain, 1.03–1.07, p < 0.001) and segmental normalization (DENSE: 1.08 per −1% peak strain, 1.04–1.12, p < 0.001, feature-tracking: 1.06 per −1% peak strain, 1.04–1.08, p < 0.001). Conclusions: Circumferential strain provides incremental prognostic value over segmental infarct size in patients post STEMI for predicting segmental improvement or normalization by wall-motion scoring.